The FUNCTION OF THE PUBLIC PROSECUTION SERVICE AHEAD THE CRISIS OF THE HUMAN RIGHTS. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The crisis of the human and basic rights in Brazil is secular subject. However, in recent years of our constitutional history, the humanitarian crisis generated the society in the direction to search solutions legitimizes and legal that can create a harmonic and established country in the State of Social welfare, taken root in rule of law. This search, inevitably, finds support in the proper Federal Constitution of 1988 that, in turn, it attributes to the Public prosecution service the duty to act in the direction to guarantee the jurisprudence and democratic, accomplishing the protection of the rights and guarantees constitutional of the Brazilian citizen. In this direction, the present article will go to display the performance accomplishes of the institute so that the bases of the basic guarantees are accomplished at moments of constitutional disequilibrium.